Considerations for Evaluating Evolving Organizations and Initiatives - Lori Palen (Journal of MultiDisciplinary Evaluation)
Background: Evaluators are often called to be flexible in response to changing programmatic and contextual circumstances. However, the field offers little guidance around issues to consider before modifying an in-progress evaluation.